Fenomena ‘No Viral No Justice’ dan Implikasinya terhadap Perlindungan Korban dalam Sistem Peradilan Pidana - Vincentius Patria Setyawan (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study aims to identify and analyze the phenomenon of “No Viral No Justice” and its implications for victim protection within the criminal justice system. It also seeks to examine the extent to which viral exposure on social media influences law enforcement responsiveness in handling cases involving victims. This research employs an empirical legal research method with a descriptive approach. The research was conducted within the jurisdiction of relevant law enforcement institutions and supported by data from media reports and victim-related cases. The types and sources of data consist of primary data and secondary data. Data collection techniques include observation, interviews, and literature study. The data were analyzed using qualitative analysis techniques. The results of this study indicate that the main factors contributing to the emergence of the “No Viral No Justice” phenomenon include lack of institutional responsiveness, limited access to justice for victims, public distrust of law enforcement, and the growing influence of social media as a tool of public pressure. Furthermore, the implications for victim protection reveal both positive and negative dimensions. On the one hand, viral exposure can accelerate case handling and strengthen institutional accountability. On the other hand, it may lead to revictimization, violations of victim privacy, and unequal protection, as only high-profile cases tend to receive serious attention. Therefore, strengthening a victim-oriented justice system that ensures equal protection without reliance on viral pressure is essential.